1990
DOI: 10.1038/hdy.1990.25
|View full text |Cite
|
Sign up to set email alerts
|

A mixed model for the effects of single gene, polygenes and their interaction on quantitative traits. 2. The effects of the nor gene and polygenes on tomato fruit softness

Abstract: The effects of the nor gene, polygenes and their interaction on tomato fruit softness one (SF1) and nine (SF9) days after picking at "breaker" stage of ripening were studied using two experimental populations, each obtained from a different cross and comprised of F3 families derived from selfed heterozygous (nor/+) F2 plants. The results were analysed using a mixed model for a single gene, polygenes and their interaction. A multiplicative nor x polygenes interaction was detected for SF1, and it was included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These authors suggested that other factors in addition to firmness are likely to be involved in the increased shelf life. Elkind et al (1990) reported that the expected effect of the nor gene will be greater in a soft genetic background. However, overall extended shelf life might be obtained in fruit with another genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that other factors in addition to firmness are likely to be involved in the increased shelf life. Elkind et al (1990) reported that the expected effect of the nor gene will be greater in a soft genetic background. However, overall extended shelf life might be obtained in fruit with another genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the major gene genotypes can be inferred from pedigree data or recognized by morphological phenotype or biochemical methods. For example, the opaque-2 gene in maize, glandless gene in cotton, nor gene in tomato (affecting fruit firmness and Table 7 Predicted genetic effects and standard errors for copula duration, developmental time, and esterase 6 activity in D. melanogaster shelf time) (Elkind et al 1990), esterase 6 gene in D. melanogaster (Gilbert 1985a), and SNPs in coding and promoter regions. Some methods thereof used ANO-VA procedure as the statistical tool (e.g., Gilbert 1985a, b;Elkind and Cahaner 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such situations are well reported, e.g., fruit softness in tomato (Elkind et al 1990), mating speed in Drosophila melanogaster (Gilbert 1985a), plant height in rice (Jiang et al 1994) and in wheat (Pinthus and Gale 1990), pest and disease resistance (vertical and horizontal resistance), and grain quality in maize (Vasal et al 1980), in rice (Kumar and Khush 1987;Mckenzie and Rutger 1983), and in barley (Tallberg 1982). For shedding light on gene expression and for making an efficient genetic improvement strategy, it is of fundamental significance to dissect phenotypic variation jointly affected by major genes and by polygenes according to corresponding constituent causes.…”
Section: Introductionmentioning
confidence: 97%
“…At times, the influence of dominant‐negative mutation such as Nac‐Nor or dominant mutation Nr may vary in different genetic backgrounds (Elkind et al , 1990; Lanahan et al , 1994; Rodríguez et al , 2010; Wang et al , 2020). Such influence was not conspicuous for Nps1 *, as in two different genetic backgrounds it dominant‐negatively stimulated carotenoids.…”
Section: Discussionmentioning
confidence: 99%